Kesalahan Berbahasa dan Penulisan Surat Dinas Kesehatan Pemerintahan Kabupaten Bone - Ahmad, Ahmad; Rahmi, Nur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to identify and analyze language errors and official letter writing within the Health Office of Bone Regency Government. The research employs a qualitative descriptive analysis method, collecting samples of official letters from the 2025 period. Data were analyzed based on linguistic aspects (spelling, diction, sentence structure) and official letter structure in accordance with the General Guidelines for Indonesian Spelling (PUEBI) and Ministerial Regulation No. 63 of 2013 on Official Correspondence.The findings indicate that the most common errors include non-standard word usage, incorrect word writing, and punctuation mistakes. The study suggests that lecturers or teachers can use these findings as a reflective tool in teaching students about language accuracy.